I doni di Eustochio e Marcella: Gerolamo e la tradizione saturnalizia (ACME, 2023)
In epist. 31 and 44 Jerome thanks his disciples Eustochium and Marcella for sending him some gifts, and interprets the objects in scriptural and moral terms. In this paper, firstly, these gifts are read in the framework of the ancient tradition of Saturnalian gift-giving: as matter of fact, they are found even in Martial’s Xenia and Apophoreta, and their Christian interpretation somewhat corresponds to ‘Saturnalian deciphering’ of gifts which is attested in some texts (e.g., Petron. 56). Moreover, Jerome seems to appropriate a widespread and widely accepted pagan tradition, in order to legitimate the new Christian nobilitas as a heir of traditional Roman aristocracy.